Integration and generalization of “Universal Test and Treat” strategies for HIV in sub-Saharan Africa : The ANRS 12249 TasP Trial and beyond - (:unkn) unknown (My University, 2017)
Increasing evidence of the preventive effect of antiretroviral treatment (ART) on HIV transmission havelaid the foundations for mathematical models to suggest that universal and repeated HIV testing,combined with immediate initiation of ART among those diagnosed HIV-positive could curtail the HIVepidemic, especially in sub-Saharan Africa. It is still unknown if this strategy, labelled as “UniversalTest and Treat” (UTT), could be workable at population level, given the unprecedented HIV servicesuptake rates that it requires.The objective of this thesis was to explore the terms of large-scale UTT implementation. Based on theprotocols of community-based trials conducted in sub-Saharan Africa, we characterized the diversity ofUTT approaches. Within the framework of one of those studies, the ANRS 12249 TasP trial, conductedin rural South Africa, we described the perceptions of health care workers regarding UTT and studiedthe care trajectories of people living with HIV from care referral to viral suppression.The findings reported in this thesis highlight that UTT strategies encompass a variety of healthinterventions, challenging the assessment of their impact on the HIV epidemic. Analyses of health careworkers opinions and patients’ behaviours when exposed to UTT underlined the potential of the strategyto change professional practices and patients’ access to care. Overall this work provides some insightson the efforts needed to allow the maximal public health impact of UTT in sub-Saharan Africa.
Keywords: African Research